Analisis Shifting Perilaku Ekonomi Masyarakat Muslim: Studi Kasus dari Pasar Tradisional ke Platform Digital di Pasar Tegal Gubug - Firyaal Faadhilah; Cory Vidianti (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The development of digital technology has led to significant changes in economic behavior, including among Muslim communities in Tegal Gubug. Economic activities that were once centered in traditional markets have now begun to shift to digital platforms such as marketplaces and social media. This study aims to examine the shift in the economic behavior of the Muslim community from direct interactions in Tegal Gubug Traditional Market to digital-based interactions in buying and selling transactions. The research employs a qualitative descriptive approach, with data collected through interviews and observations of Muslim traders and consumers who have transitioned to using digital platforms. The findings reveal that the main factors driving this shift are ease of access, time efficiency, and the expansion of marketing networks. However, the study also identifies challenges such as reduced direct social interaction among economic actors and a lack of understanding regarding the application of Islamic business ethics in the digital space. This research emphasizes the importance of internalizing Islamic values such as honesty, justice, and responsibility in every digital economic activity to ensure alignment with sharia principles.